AI-Powered KMAP: An Enterprise Intelligence Model for Organizational Knowledge Transformation - Soleh, Alvin; Fadhilah, Pinkan (JURNAL MANAJEMEN MOTIVASI, 2026)
This study develops a conceptual framework of AI-Powered Knowledge Map (KMAP) to address organizational knowledge management challenges. Using a conceptual design through literature synthesis, this study proposes KMAP as an intelligent enterprise hub integrating strategy, processes, capabilities, and organizational learning. The framework consists of ten conceptual pillars that explain AI's role in activating knowledge and bridging the strategy–execution gap. Results imply that AI-KMAP enhances decision quality, supports adaptive learning, and transforms knowledge into performance-oriented organizational intelligence.